Job stress among academic staff: The case of community colleges in Pahang - Norliana, Ali (2015)
The purpose of this study is to identify the relationship between role conflict, role ambiguity, job promotion, working conditions and workloads to job stress. The survey method was used to collect the primary data through the use of a questionnaire to the community college academic staff in Pahang. 103 of questionnaire were distributed and all 103 questionnaires were successfully collected. The descriptive and inferential analyses were conducted. The results of this study showed that role conflict, role ambiguity, job promotion, working conditions and workloads are all positive correlated to job stress. Role conflict, workloads and job promotion are moderately correlated with job stress. While role ambiguity and working conditions factors is low correlation to job stress. This results of this study provides information about job stress among college community academic staff in Pahang to policy maker for improvement the community college management